دور بعض العوامل البشرية في تحسين الانتاجية : دراسة استطلاعية لآراء المدراء في الشركة العامة للسمنت الشمالية - نبيل حازم محمد الشيخ (PROSPECTIVE RESEARCHES, 2023)
The word “productivity” is first mentioned in the 18th century in a research of the French econmist (Franswa Kenai) in 1766. The beginging of the 20th century witnessed many countries interest in the researches and applied academic studies about productivity, its measuring methods and factors affecting it. However, in spite of the oldness of productivity subject, the current rapid scientific and technological progress have participated in increasing competition among most countries and enterprises; pushing them toward increasing consideration of scientific research in this subject, determination of factors affecting it and treatment of its reduction reasons in order to raise its competition capabilities in global markets. The studies carried about productivity indicate that there are a number of factors affecting its improvement; human factors come in the first place. So, this research is oriented to study the role of some humaneness factors in improving productivity by application in the Northern state Company of cement via studing the most affecting factors in promoting productivity theoretically and studying the role of some human factors such as organizational environment, labor force structure, wages and motivations. The data were collected depending on a five folds interval questionaire form to measure and test the research variables, the statistical program SPSS V.18 has been used to process data. The research has come up with a number of results like: There is a positive correlation and effect between human factors and productivity. Also, the research has presented a number of recommendations like: Concentrating on both materialistic and morale motivations and the fairness in giving these motivations should be considered due to their direct impact on improving workers productivity and establishing the process of workers training as its one of the main elements affecting productivity improvement.